Correlates of Physicians' and Patients' Language Use during Surgical Consultations. Issue 10 (23rd August 2020) - Tran, Brandon Q.; Sweeny, Kate
ABSTRACT: A multi-method approach was used to explore correlates of technical and complex language use within 145 audio-recorded physician-patient interactions. When discussing the prospect of surgery, physicians used more technical and complex language (more jargon, larger words, longer sentences) than patients on average. Patients' demographic characteristics (education, health literacy, English fluency) and markers of health (condition severity) inconsistently predicted physicians' and patients' use of complex and technical language. Interactions with happier and more hopeful patients involved less technical and complex language, but physicians' language use was unrelated to patients' emotions following the consultation. Finally, physicians' use of more technical language predicted greater patient satisfaction following the consultation, and physicians' use of more complex language at the initial consultation predicted better adherence by patients following surgery. Our results highlight the nuanced role of language use within healthcare interactions and identifies language complexity as a novel target for health communication research.